Progressive multifocal leukoencephalopathy, more than an encephalopathy - David Sáez M; Nadia Valdés R; Cristian Fernández M; Rocío Pacheco E (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2022)
Progressive multifocal leukoencephalopathy is a pathology associated with the presence of the JC virus, although it occurs in other conditions, nowadays most cases occur in patients with AIDS, in severe stages of immunosuppression. This condition, and hence its name, has always been associated with the presence of intracerebral lesions, where it can have a wide distribution. However, it is very rare, if ever, to report lesions of this disease in the spinal cord. We present a case of a 40-year-old patient, an HIV carrier in the AIDS stage, who, in addition to presenting brain lesions, had multiple lesions at the cervical spinal cord level. We believe that these lesions may be more common than believed and should be intentionally sought if possible.